Interview with Kumudini Dakua, leader of the Tamralipta uprising against British colonial rule in 1942-1945, interviewed by Kabir in Midnapur, West Bengal - Kabir, Shahriar.
Interview with Kumudini Dakua, leader of the Tamralipta uprising against British colonial rule in 1942-1945, interviewed by Kabir in Midnapur, West Bengal.